The Influence of Organizational Culture and Individual Characteristics on Employee Performance with Work Experience as a Moderating Variable in Bpjs Employment Branch Offices in Aceh Raya - Ikhlasul Amal Maulana; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
This study aims to see the Influence of Organizational Culture and Individual Characteristics on Employee Performance with Work Experience as a Moderation Variable in BPJS Employment Branch Office in Aceh Raya The type of research used by the researcher is quantitative research, The population and sample in this study are all permanent employees at PT. BPJS Employment Banda Aceh Branch Office totals 70 employees (saturated sample). The data analysis in this study uses Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of this study are as follows: Organizational Culture has a positive and significant effect on Employee Performance with an original sample value of 0.334 and p values of 0.007. Individual Character had a positive and insignificant effect on Employee Performance with the original sample value of 0.382 and p values of 0.069. Work experience had a positive and insignificant effect with the original sample value of 0.258 and p values of 0.147. Organizational culture had a positive and insignificant effect on Employee Performance and work experience was not able to moderate with the original sample results of 0.079 and p values of 0.671. Individual characteristics have a negative and insignificant effect and are moderated by work experience with the original sample value of -0.084 and p values of 0.597.